Pengaruh Pemahaman Kode Etik Akuntan, Kecerdasan Spiritual Dan Kecintaan Pada Uang Terhadap Persepsi Mahasiswa Akuntansi Mengenai Perilaku Etis Akuntan - Eldi; Rinaldy, Syiar (Insan Cita Bongaya Research Journal, 2024)
his research aims to test the understanding of the accountant's code of ethics, spiritual intelligence, love of money on the ethical perceptions of accounting students regarding the ethical perceptions of accountants. The population was Stiem Bongaya accounting students class 2020, 2021 and 2022. The sampling technique used was Purposive Sampling. Thus, the number of samples used in this research was 175 accounting students. The analysis technique used is multiple linear regression. The results of the questionnaire data have been tested with classical instruments and assumptions in the form of normality, heteroscedasticity and multicollinearity assumptions. The data analysis method uses multiple linear regression techniques. The results of this research show that understanding the professional code of ethics for accountants has a positive effect, while spiritual intelligence and love of money have a negative effect on students' ethical behavior.